PERAN KOMUNITAS BELAJAR DALAM MEMBANGUN BUDAYA KERJA TIM YANG EFEKTIF DI SD NEGERI 11 JAMBU - Fitri Roihani; Sukarman; Ahmad Muslim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to evaluate the role of learning communities in building an effective team work culture at SD Negeri 11 Jambu. This research employs a qualitative case study approach involving observation, documentation, and interviews. The results indicate that learning communities enhance collaboration, communication, and collective responsibility among teachers, leading to a productive team work culture that supports the improvement of professional competence. To establish a learning community, school management must provide support despite challenges such as limited time and varying levels of participation. Therefore, learning communities are an effective way to strengthen team work culture and improve the quality of education in elementary schools. The study recommends strengthening management support and sustainable participation mechanisms.